2002
DOI: 10.1038/nature01231
|View full text |Cite
|
Sign up to set email alerts
|

HAR1 mediates systemic regulation of symbiotic organ development

Abstract: Symbiotic root nodules are beneficial to leguminous host plants; however, excessive nodulation damages the host because it interferes with the distribution of nutrients in the plant. To keep a steady balance, the nodulation programme is regulated systemically in leguminous hosts. Leguminous mutants that have lost this ability display a hypernodulating phenotype. Through the use of reciprocal and self-grafting studies using Lotus japonicus hypernodulating mutants, har1 (also known as sym78), we show that the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
414
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 483 publications
(437 citation statements)
references
References 27 publications
7
414
0
6
Order By: Relevance
“…Mutations in En 1314 and En 1282 soybeans were found in the NFR1 gene, which is known to be responsible for a LysM-type receptor kinase for Nod factor recognition (Radutoiu et al, 2003 Masaki Hayashi (National Institute of Agrobiological Sciences, Tsukuba, Japan), personal communication). A mutation in En 6500 was found in the GmNARK (NTS1) gene (Nishimura et al, 2002), which mediates systemic autoregulation of nodulation (Searle et al, 2003), and Sakukei 4 is a descendant with a hypernodulating phenotype that was derived from En 6500 (Matsunami et al, 2004).…”
Section: Plant Materials and Field Experimental Designmentioning
confidence: 99%
“…Mutations in En 1314 and En 1282 soybeans were found in the NFR1 gene, which is known to be responsible for a LysM-type receptor kinase for Nod factor recognition (Radutoiu et al, 2003 Masaki Hayashi (National Institute of Agrobiological Sciences, Tsukuba, Japan), personal communication). A mutation in En 6500 was found in the GmNARK (NTS1) gene (Nishimura et al, 2002), which mediates systemic autoregulation of nodulation (Searle et al, 2003), and Sakukei 4 is a descendant with a hypernodulating phenotype that was derived from En 6500 (Matsunami et al, 2004).…”
Section: Plant Materials and Field Experimental Designmentioning
confidence: 99%
“…The position mapped for OL2168 was the same as that of har1 (Nishimura et al 2002a). OL2168 developed shorter taproots and a large number of lateral roots.…”
Section: Resultsmentioning
confidence: 66%
“…In the known mutants of hypernodulation, several peculiar non-symbiotic characteristics were found that differed from the wild-type plant. The har1 plant develops a greater number of lateral roots than the wild-type plant (Kawaguchi et al 2002;Nishimura et al 2002a), whereas the mutant clavier is a dwarf with delayed flowering and a different morphology of leaf veins (Oka-Kira et al 2005). The mutant astray exhibits characteristics that are associated with defects in light and gravity responses (Nishimura et al 2002b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations